Rh(iii)-Catalyzed regioselective C–H [4 + 2] C-annulation of vinyl enaminones with alkynes to form polysubstituted salicylaldehydes. Issue 19 (12th September 2018) - Zhao, Yinsong; Zheng, Qinze; Yu, Chuangui; Liu, Zheng; Wang, Deping; You, Jingsong; Gao, Ge
Abstract : Sterically congested polysubstituted salicylaldehydes are accessed through a Rh(iii )-catalyzed regioselective vinylic C–H [4 + 2] C -annulation reaction of vinyl enaminones with alkynes. Abstract : A Rh(iii )-catalyzed regioselective C–H [4 + 2] C -annulation reaction of vinyl enaminones with alkynes is developed to provide sterically congested polysubstituted salicylaldehydes. This reaction shows relatively broad substrate scope with good functional group tolerance. The applications of this method to prepare useful synthetic precursors and bioactive skeletons are also exemplified.